Vhl deletion in Dmp1-expressing cells alters MEP metabolism and promotes stress erythropoiesis - Emery, Janna M.; Chicana, Betsabel; Taglinao, Hanna; Ponce, Citlaly; Donham, Cristine; Padmore, Hawa; Sebastian, Aimy; Trasti, Scott L.; Manilay, Jennifer O. (Frontiers in Hematology, 2024)
Erythropoiesis occurs in a specialized niche in the bone marrow and is regulated in part by oxygen-sensing signaling pathways. VHL is an E3 ubiquitin ligase that regulates the degradation of hypoxia-inducible factor (HIF) proteins under normoxic conditions. In hypoxia, VHL is inactivated resulting in enhancement of HIF signaling. To investigate the effects of HIF-activation in bone cells on erythropoiesis, we performed longitudinal analyses of conditional Vhl knockout mice (Dmp1-Cre;Vhlfl/fl; VhlcKO) mice, in which Vhl is deleted primarily in osteocytes but is retained in hematopoietic cells. VhlcKO mice display elevated red blood cell counts and erythropoietin levels starting at 10 weeks of age, resembling polycythemia. Using flow cytometry, we observed increased frequency of CD71loTER119hiFSClo orthochromatophilic erythroblasts and reticulocytes in 10- and 24-week-old VhlcKO bone marrow. Features of extramedullary hematopoiesis were observed in the spleen, including red pulp hyperplasia, the presence of megakaryocytes, and increased frequency of basophilic and polychromatophilic erythroblasts and of mature stress erythroid progenitors. To investigate the mechanisms that drive the accelerated erythropoiesis in the bone marrow, we enumerated myeloid progenitors and observed higher frequencies of megakaryocyte-erythroid progenitors (MEPs) at 6 and 10 weeks of age, but MEP frequency was similar to controls at 24 weeks. Despite this normalization in MEP frequencies, bulk RNA-Seq of MEPs at this age showed upregulation of Epas1 (Hif2a), consistent with a response to hypoxia, as well as genes involved in erythrocyte development. Surprisingly, genes involved in the response to glucose were also upregulated in VhlcKO MEPs. Our studies implicate that HIF-driven alterations in skeletal homeostasis drive changes to the bone marrow microenvironment that influence erythroid cell development and MEP metabolism.